The Relationship of Nahwu and Al-Qur'an Sciences - Suratno, Suratno; Af’idah, Miftah Inayatul (Global Research Network, 2024)
As a branch of linguistics, it occupies an important position in Arabic language activities. This is because Nahwu concerns sentence structure, or how a word's position in a sentence is discussed. The Qur’an, as a guide for Muslims who speak Arabic, certainly has a lot to do with the science of Nahwu. Therefore, using a research library and a qualitative approach, the author is interested in researching the relationship between nahwu science and sciences related to the Koran. This research reveals the relationship between nahwu science and sciences related to the Qur’an, such as tafsir, qiroat, history, and tahfidz.